Wet diaper detection and notification device to alert the baby caretaker - Burhannuddin, Dirman Hanafi; Mazlan, Sulaiman; Abdul Rahman, Hisyam; Abdul Rahim, Ruzairi (UTM Press, 2022)
Diapers have been popular with parents for a past few decades now for protecting babies/children from urine when they urinate. However, there are some disadvantages when using diapers such as skin rash, irritation, and infection. Skin rashes can occur when the diaper is wet with urine and left to be used for a long time with the baby. This paper aims (i) to develop wet diaper detection and notification device for helping caretakers identify wet diaper conditions, (ii) to evaluate the performance of the wet diaper detection and notification device based on the response time to trigger notification after detecting wet diaper condition. The methods of this study were divided into four phases including project design, algorithm development, hardware development, and performance evaluation. This system serves to identify the wet diaper condition based on temperature and humidity values. DHT22 was selected as a main sensor and Arduino pro mini was selected as the microprocessor for this project. As the results, two wet diaper detection and notification devices have been designed and fabricated. Comparisons have been made to evaluate the performance between the first and second versions of the devices. The performance of second version device resulting better response time with 1700ms to notify the caretaker when detecting the wet diaper condition.